Training on Strengthening Social Networks and Collaboration Between Group Members to Improve the Welfare of Rice Farmers in Cialam Jaya Village, Konda District, South Konawe Regency - Sarpin; Supiyah, Ratna; Arsyad, Muhammad; Hos, Jamaluddin; Suaib, Eka; Bahtiar; Ridwan, Harnina; Peribadi; Roslan, Suharty; Yusuf, Bakri (CV. Literasi Indonesia, 2025)
The community service program in Cialam Jaya Village, Konda District, South Konawe Regency, is designed with a participatory approach and holistic experiential learning-based training methods. This training aims to strengthen the social network and collaboration of rice farmer groups through a series of activities such as directed group discussions, field practice simulations, and mentoring by cross-disciplinary experts. The training process begins with a needs assessment, then continues with the preparation of training modules and the implementation of skills through direct practice, followed by the stage of collective evaluation and reflection. The results of the activity showed a positive impact in the form of increased communication, trust, and cooperation between farmers. In addition to technical improvements such as irrigation efficiency and crop diversification, the training also succeeded in strengthening interpersonal capacities, such as shared decision-making and conflict management. The evaluation showed an increase in productivity, active participation of farmers, and the emergence of collective farming initiatives. Alternative strategic solutions such as regular communication forums, mentoring of superior farmers, and the integration of technology based on local wisdom also support the sustainability of program results. This service proves that contextual and collaborative approaches can encourage socio-economic transformation and strengthen village independence based on sustainable agriculture.